Characterization of Metal‐zeolite Composite Catalysts: Determining the Environment of the Active Phase. Issue 7 (22nd January 2020) - Juneau, Mitchell; Liu, Renjie; Peng, Yikang; Malge, Akhilesh; Ma, Zhiqiang; Porosoff, Marc D.
Abstract: Metal‐zeolite composite catalysts are attracting increased attention due to their unique multifunctional properties. However, it is challenging to identify the physicochemical environment of the active phase, which is essential to improve our understanding of the structure‐performance relationships of such complex catalysts. In this work, commonly available analytical techniques (FTIR, TEM, XRD, etc.) and state‐of‐the‐art user instrumentation (XAS, SANS, e‐TEM, etc.) are reviewed with respect to their applications at different stages of the catalyst lifetime, from early nucleation, to the reaction mechanism and deactivation. Each technique is discussed in detail with examples to provide suggestions and guidelines for choosing the characterization technique(s) that are most appropriate for determining the desired structure‐property relationships of metal‐zeolite composite catalysts. Understanding the most appropriate applications of characterization techniques promotes development of novel synthesis methodologies, and in turn, applications for designing active, selective and stable multifunctional metal‐zeolite composite catalysts. Abstract : Characterizations reviewed : Microscopy and spectroscopy tools are applied to determine the active phase in metal‐zeolite composite catalysts.